Evaluating the United Nation’s Agenda for Atrocity Prevention: Prospects for the International Regulation of Internal Security - Jacob, Cecilia (2015)
In recent years the UN Secretary-General has promoted mass atrocity prevention as the priority agenda for the Responsibility to Protect (R2P) at the UN, redirecting debates on R2P away from military interventionism towards improved state capacity to prevent atrocity crimes and protect populations. This focus has been illustrated in the UNSG’s annual reports on R2P since 2009, and the 2014 “Framework of Analysis for Atrocity Crimes”, that emphasise state institutional capacity and the identification of atrocity-risk indicators. Through a case-study of Pakistan, this article problematizes the relationship between internal security and the UN agenda on atrocity prevention to evaluate the viability of promoting atrocity prevention as currently conceived by the Office of the UNSG in high-risk contexts. It argues that an atrocity prevention agenda informed by a responsive regulation framework would be more effective in taking into account the relational dynamics of atrocity crimes. This includes accounting for the interaction between the micro-dynamics of political violence with macro-dynamics created by lengthy historical conflicts and strategic repertoires.